Salting-out effect of sodium carbonate on the liquid–liquid equilibrium of (Water + Dichloromethane + N, N-Dimethylacetamide) system at temperature T=(298.15 and 308.15) K. Issue 7 (3rd May 2019) - Li, Jing; Liu, Chunlai; Wang, Chengxue; Diao, zhenheng
ABSTRACT: The salting-out effect of sodium carbonate (Na2 CO3 ) on the liquid–liquid equilibrium (LLE) of the ternary system of {water + dichloromethane + N, N-dimethylacetamide (DMAC)} was studied at temperature T  = (298.15 and 308.15) K and atmospheric pressure. The generated data for salt-free system have been used to estimate the binary interaction parameters for the nonrandom two-liquid (NRTL) activity coefficient model. The mass fraction of the added salt is 2% or 5% of the initial water. Adding a 0.02 mass fraction Na2 CO3 leads to an average enhancement of about 147% in distribution coefficient of DMAC between two phases, and it reaches to about 227% by adding 0.05 mass fraction of the salt. Isoactivity condition, the binary subsystems consistency and the tie-lines consistency have been verified in this paper and the K -value method is used for LLE data correlation. The root-mean-square deviation of the system was calculated in order to detect the correlation and accuracy of the NRTL model.